2011
DOI: 10.1107/s0909049511023727
|View full text |Cite
|
Sign up to set email alerts
|

Microprobing the molecular spatial distribution and structural architecture of feed-type sorghum seed tissue (Sorghum Bicolor L.) using the synchrotron radiation infrared microspectroscopy technique

Abstract: Sorghum seed (Sorghum bicolor L.) has unique degradation and fermentation behaviours compared with other cereal grains such as wheat, barley and corn. This may be related to its cell and cell-wall architecture. The advanced synchrotron radiation infrared microspectroscopy (SR-IMS) technique enables the study of cell or living cell biochemistry within cellular dimensions. The objective of this study was to use the SR-IMS imaging technique to microprobe molecular spatial distribution and cell architecture of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 30 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Spectral signatures of single pollen grains show strong Mie scattering due to their nearly perfect spherical shape (Lukacs et al 2015). In comparison, nearly perfect absorbance spectra have been obtained, when plant materials have been probed by FTIR microspectroscopy as thin sections (Fackler and Thygesen 2013;Yu 2011). Mie scattering signatures are difficult to remove by spectral pre-processing methods.…”
Section: Advantages and Limitations Of Vibrational Microspectroscopiementioning
confidence: 99%
See 1 more Smart Citation
“…Spectral signatures of single pollen grains show strong Mie scattering due to their nearly perfect spherical shape (Lukacs et al 2015). In comparison, nearly perfect absorbance spectra have been obtained, when plant materials have been probed by FTIR microspectroscopy as thin sections (Fackler and Thygesen 2013;Yu 2011). Mie scattering signatures are difficult to remove by spectral pre-processing methods.…”
Section: Advantages and Limitations Of Vibrational Microspectroscopiementioning
confidence: 99%
“…Regarding that plant cells are on average some of the largest eukaryotic cells, in general both techniques have sufficient spatial resolution for the analysis of plant cells and tissues. FTIR and Raman have been applied extensively on various plant structures, such as cell walls, seeds, and leaves, for research on plant physiology, developmental biology, genetics and ecology (Gorzsas et al 2011;Barron et al 2005;Dokken et al 2005;Chen et al 2013;Yu 2011;Gierlinger and Schwanninger 2006;Chylińska et al 2014;Agarwal 2006;Fackler and Thygesen 2013;Gierlinger et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…A brief review of this area and its potential has recently been published, 18 and a number of other studies have tackled the approach of studying stem cell differentiation in a label-free manner. [19][20][21][22] One such method that is currently being developed is infrared micro-spectroscopy. Infrared spectroscopy of single cells was first demonstrated by Jamin et al 23 in the late 1990s using synchrotron radiation generated infrared as the light source.…”
Section: Introductionmentioning
confidence: 99%
“…Yu [5] reported that the advanced Synchrotron-Radiation Infrared MicroSpectroscopy (SR-IMS) is able to study cell or living cell biochemistry within cellular dimension [4]. The author used the SR-…”
Section: Application A: Microprobing Molecular Spatial Distribution Amentioning
confidence: 99%